2022
DOI: 10.7883/yoken.jjid.2021.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Neisseria gonorrhoeae </i>in Western Iran

Abstract: Neisseria gonorrhoeae is the causative agent of the sexually transmitted disease gonorrhoea. This bacterium infects the epithelial cells of the cervix of women and the urethra of men. However, its disease symptoms in the lower genitalia are found only in a small percentage of people. This study aimed to compare the frequency of N. gonorrhoeae genital infection among two groups of pregnant women, those with spontaneous abortions and those with normal pregnancies. This crosssectional study was conducted in Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In addition, in the northern provinces of Iran, the prevalence of N. gonorrhoeae was 0.2% [14]. Moreover, in the studies from Zanjan and Kurdistan prevalence of the N. gonorrhoeae was less than %1 [1,15]. On the other hand, other studies from Iran reported more close prevalence rate for N. gonorrhoeae to the current study's results.…”
Section: N Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…In addition, in the northern provinces of Iran, the prevalence of N. gonorrhoeae was 0.2% [14]. Moreover, in the studies from Zanjan and Kurdistan prevalence of the N. gonorrhoeae was less than %1 [1,15]. On the other hand, other studies from Iran reported more close prevalence rate for N. gonorrhoeae to the current study's results.…”
Section: N Discussionsupporting
confidence: 45%
“…According to previous studies in Iran, the positive culture rate of N. gonorrhoeae has been reported from zero to less than 2% [1,10,11]. According to the low sensitivity of culture and phenotypic tests for detection of N. gonorrhoeae, C. trachomatis, and Mycoplasma species, conventional microbial diagnostics were targeted in this study only to detect S. agalactiae.…”
Section: N Discussionmentioning
confidence: 99%
See 1 more Smart Citation